Midwives' readiness for handling postpartum Perinatal Mental Health (PMH) disorders: a mixed-methods study - Harahap, Ana Pujianti; Amini, Aulia; Setyowati, Dina Lusiana; Basrowi, Ray Wagiu; Yuliana, Roma (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
Perinatal mental health (PMH) disorders affect 15.6–37% of postpartum women, yet midwives report low confidence in detection and management due to inadequate training and protocols. This study evaluated midwives' readiness to handle postpartum PMH disorders in community health centers. A convergent parallel mixed-methods design was used in eight Mataram City health centers (December 2023–January 2024). Quantitatively, 102 purposively sampled midwives completed validated questionnaires on sociodemographics, screening practices, and PMH handling, analyzed via chi-square tests. Qualitatively, thematic analysis of in-depth interviews with six informants (managers, midwives, and mental health nurses) explored referral experiences using N-Vivo. Most midwives (86.27%) did not handle PMH appropriately. The implementation of PMH data assessment (37.25%), screening (37.26%), and classification (22.56%) was low. Handling PMH significance association with screening (p=0.001, OR 14.31), classification (p=0.001, OR 23.22), and data assessment (p=0.009, OR 9.43). Age, education, experience, and training were not associated. Themes emphasized referral collaboration with family consent, consultation with mental health nurses/doctors, and hospitalization for the most serious cases. Midwives are not yet sufficiently prepared to address the perinatal mental health (PMH) needs of postnatal women. Poor screening uptake is a consequence of the absence of protocols and time limitations, and this highlights requirements for training and standardized pathways. Referral dependence is compensatory but inconsistent, mirroring global appeals for inter-professional approaches. Targeted PMH training and referral protocols are crucial in order to assist the development of midwives' skills to provide prompt care and reduce maternal-infant risk. Interventions should be tested in longitudinal studies across a variety of Indonesian contexts.